2019
DOI: 10.1136/bmjopen-2018-027276
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinant factors of anaemia among women of reproductive age in Ethiopia: a multilevel and spatial analysis

Abstract: ObjectiveThe aim of this study was to assess the spatial distribution and determinant factors of anaemia among reproductive age women in Ethiopia.MethodsAn in-depth analysis of the 2016 Ethiopian Demographic and Health Survey data was undertaken. Getis-Ord Gi* statistics were used to identify the hot and cold spot areas for anaemia among women of reproductive age. A multilevel logistic regression model was used to identify independent predictors of anaemia among women of reproductive age.ResultsOlder age (adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
86
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 45 publications
32
86
4
Order By: Relevance
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly (18).…”
Section: Discussionsupporting
confidence: 92%
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly (18).…”
Section: Discussionsupporting
confidence: 92%
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly explained by the low economic and human development in these regions.…”
Section: Discussionsupporting
confidence: 92%
“…The causes and environmental drivers of anemia showed a high degree of geographic clustering (10). A growing body of evidence indicated that Hb concentration (anaemia) is clustered geographically (10)(11)(12)(13)(14). A study on spatial heterogeneity of Hb concentration in sub Saharan Africa showed that Hb concentration among preschool children was highly clustered geographically in both western and eastern Africa (10,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, These regions also are relatively rural residents and that they couldn't access health facilities and ladies might not have awareness about the iron supplementation program and its bene t during their pregnancymight not have good access to maternal health care services. In several studies also evidence showed that in Somali,Hareri, and Afar regions the prevalence of anemia among reproductive-age women was high ( (22,23). The nding of multilevel multivariable logistic regression indicated that ANC visits, community women's education, region, media exposure, household wealth index, and distance to the clinic as associated factors of iron supplementation use among pregnant women in Ethiopia.…”
Section: Discussionmentioning
confidence: 97%